Algorithmic Performance Management in Higher Education: Viva! 365 Ways of Surveillance - Heemsbergen, Luke; Krebs, Shiri; Gorur, Radhika; Maddox, Alexia (Surveillance & Society, 2024)
This paper maps the emergence and consequences of automated Algorithmic Performance Management (APM) in the context of higher education. After reviewing the evolution of productivity management in academia, it argues that surveillance via APM shifts expectations not just about effectiveness at work but also about how work, and the good worker, come to be defined. In our paradigmatic case study of Office 365, we specify how the automated surveillance of workforce practices are deployed to redefine productivity in higher education: productive workers become good data subjects as well as producers of papers, grants, and other traditional outputs of success. Our analysis suggests performing well at work is managed in and by the platform via logics of the surveillance of wellness, time-regulation, and social connectivity to influence, manage, and control workers. We critique these automated performance measures in terms of platform capitalism, noting Office 365’s Viva Insights function as a telematic device of surveillance. The final section of the paper places these trends in Australia’s socio-legal context by showing how Viva is insufficient for considering performance given the range of practices that constitute “academic work,” including but not limited to the need for unmonitored activity. Yet, we observe that currently little can be done about Office 365’s surveillant presence given a regulatory regime that by and large excludes productivity surveillance from the scope of regulated surveillance activities.